Qualifying EFL Student Teachers Cross-Culturally and Humanely for Promoting Social Justice - Rass, Ruwaida Abu (International Journal of Social Sciences and English Literature, 2025)
This qualitative research study investigates the contribution of a course called Multiculturalism in Literature for 52 Arab Muslim student teachers who were pursuing their B.Ed. majoring in teaching English as a Foreign Language (EFL) in the central part of Israel. The course exposed them to cultural diversity, conflicts, and processes of adjustment of Indigenous peoples and immigrants in English-speaking countries. Data collection included analyzing their reflections, which showed that the course helped them promote their cross-cultural competence, raise their awareness of issues of social injustice, and feel empowered. It can be concluded that integrating such a course would help qualify EFL teachers not only linguistically but also cross-culturally and humanely as agents for social change.